PENGARUH FASILITAS KERJA DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA BKPSDM TANGERANG SELATAN - Asjimi, Risky; Utama, Rony Edward (Taksasila Edukasi Insani, 2023)
This research aims to determine the effect of work facilities on employee performance, to determine the effect of work discipline on employee performance. The population in this study were employees of the Human Resources and Human Resources Development Agency (BKPSDM), totaling 40 employees. Hypothesis testing uses an associative research design, statistical analysis methods consisting of multiple linear regression analysis, partial testing (t test) and testing the coefficient of determination. Research results on partial testing (t test). Shows that the Work Facilities variable has a positive and significant effect on employee performance, the Work Discipline variable has a positive and significant effect on employee performance. There is a positive and significant influence between work facilities and work discipline together on employee performance. And through testing the coefficient of determination (Adjusted R Square), a value of 0.818 or 81.8% was obtained. This means that employee performance is influenced by work facilities and work discipline by 81.8%. while the remaining 18.2% is determined by other variables. Keywords : Employee Performance, Work Facilities, and Work Discipline.